Stakeholders Analysis of Policy-Making Process: The Case of Timber Legality Policy on Private Forest - Mulyaningrum Mulyaningrum; Hariadi Kartodihardjo; I Nengah Surati Jaya; Bramasto Nugroho (Institut Pertanian Bogor (IPB University), 2013)
The objective of the study is to identify and measure the relationships among stakeholders that influence the process of policy-making in defining legality of timber from private forests. The study focuses on the policy-making process of the Ministry of Forestry Regulation P.38/Menhut-II/2009 on Standard and Guidelines for Assessment of Sustainable Forest Management Performance and Timber Legality Verification of Concessionaire or of the Private Forest License Holder as the subject that has been implemented in several private forest management units as follow: Giri Mukti Wana Tirta in Lampung, Koperasi Serba Usaha APIK in Bali, Koperasi Hutan Jaya Lestari in South East Sulawesi, and Koperasi Wana Lestari Menoreh Kulonprogo in Yogyakarta. This research used a qualitative approach and the analysis method used in this research is a modified-stakeholder analysis that developed by ODA (1995), Reitbergen et al. (1998), and Mayer (2005). The stakeholder analysis shows that the interests and influences do not consider private forest farmers as primary stakeholder during the process of policy formulation. The strong national and international interests, supported by high authority could not be influnced by the role of the NGOs and academicians. The imbalance of responsibilities, rights, and revenues that was experienced by farmers as the manager of private forest when started implementing the policy was more as burdens, it means implementation of the policy was more as burdens. Strong relationships between the Ministry of Forestry with the state as a core could not empower the relationship with private forest farmers. As result, policy assumptions cannot be implemented properly.